14-day toxicity studies of tetravalent and pentavalent vanadium compounds in Harlan Sprague Dawley rats and B6C3F1/N mice via drinking water exposure. (2016) - Roberts, Georgia K.; Stout, Matthew D.; Sayers, Brian; Fallacara, Dawn M.; Hejtmancik, Milton R.; Waidyanatha, Suramya; Hooth, Michelle J.
Abstract: Background: The National Toxicology Program (NTP) performed short-term toxicity studies of tetra- and pentavalent vanadium compounds, vanadyl sulfate and sodium metavanadate, respectively. Due to widespread human exposure and a lack of chronic toxicity data, there is concern for human health following oral exposure to soluble vanadium compounds. Objectives: To compare the potency and toxicological profile of vanadyl sulfate and sodium metavanadate using a short-term in vivo toxicity assay. Methods: Adult male and female Harlan Sprague Dawley (HSD) rats and B6C3F1/N mice, 5 per group, were exposed to vanadyl sulfate or sodium metavanadate, via drinking water, at concentrations of 0, 125, 250, 500, 1000 or 2000 mg/L for 14 days. Water consumption, body weights and clinical observations were recorded throughout the study; organ weights were collected at study termination. Results: Lower water consumption, up to −80% at 2000 mg/L, was observed at most exposure concentrations for animals exposed to either vanadyl sulfate or sodium metavanadate and was accompanied by decreased body weights at the highest concentrations for both compounds. Animals in the 1000 and 2000 mg/L sodium metavanadate groups were removed early due to overt toxicity. Thinness was observed in high-dose animals exposed to either compound, while lethargy and abnormal gait were only observed in vanadate-exposed animals. Conclusions: Based on clinical observations and overt toxicity, sodium metavanadate appears to be more toxic than vanadyl sulfate. Differential toxicity cannot be explained by differences in total vanadium intake, based on water consumption, and may be due to differences in disposition or mechanism of toxicity.